Rapid start-up of a bioelectrochemical system under alkaline and saline conditions for efficient oxalate removal - Weerasinghe Mohottige, T.; Ginige, M.; Kaksonen, A.; Sarukkalige, Priyantha Ranjan; Cheng, K. (Elsevier BV, 2018)
This study examined a new approach for starting up a bioelectrochemical system (BES) for oxalate removal from an alkaline (pH > 12) and saline (NaCl 25 g/L) liquor. An oxalotrophic biofilm pre-grown aerobically onto granular graphite carriers was used directly as both the microbial inoculum and the BES anode. At anode potential of +200 mV (Ag/AgCl) the biofilm readily switched from using oxygen to graphite as sole electron acceptor for oxalate oxidation. BES performance was characterised at various hydraulic retention times (HRTs, 3–24 h), anode potentials (-600 to +200 mV vs. Ag/AgCl) and influent oxalate (25 mM) to acetate (0–30 mM) ratios. Maximum current density recorded was 363 A/m 3 at 3 h HRT with a high coulombic efficiency (CE) of 70%. The biofilm could concurrently degrade acetate and oxalate (CE 80%) without apparent preference towards acetate. Pyro-sequencing analysis revealed that known oxalate degraders Oxalobacteraceae became abundant signifying their role in this novel bioprocess.